Pengetahuan Gizi, Kebiasaan Minum Dan Asupan Karbohidrat Antara Remaja Sudah Overweight Dan Tidak Overweight Di SMP 03 Doplang - ARNI, Atria Tyas; , Endang Nur W, S.St., M.Si.Med; , Eni Purwani, S.Si., M.Si (2015)
Introduction: overweight are overweight because of an inefficient provision of energy consumption and kebutuhanya. An overweight teen will need more water than not overweight. This is because teens are overweight have metabolic burden is higher compared to that of normal weight have. Purpose: the purpose of this research is to know the difference in nutritional knowledge, habits of drinking and carbohydrate intake among adolescent overweight and non overweight. Research methods: obsevasional research with cross sectional approach, housed in junior high with the number of samples doplang 03 25 adolescents overweight and 25 teenagers non-standard overweight selected by stratified random sampling. The data collected includes the knowledge of nutrition, drinking habits and carbohydrate intake. Nutritional knowledge is measured using a questionnaire, the habit of drinking was measured using the FFQ and carbohydrate intake was measured using the 24-hour recall. Results: overweight teenagers on knowledge of good nutrition as much as 20% while the non overweight adolescents while 32% with p = 0.698. carbohydrate intake in adolescent overweight by category less as much as 92% while the non overweight 96% with p = 0091 may. the habit of drinking by category less on adolescent overweight by as much as 76% while the non overweight by as much as 24% with p = 0.053. Conclusion: there is no difference in nutritional knowledge, habits of drinking and carbohydrate intake among adolescent overweight and non overweight.